Agricultural commodities and processed products ratio in the Romanian international agrifood trade - Camelia Gavrilescu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
Romania's international agrifood trade increased significantly during the last decade, and mostly after the EU accession. Since 1990, the Romanian agrifood trade balance showed an almost continuous increasing deficit trend until 2008. In four years only, the trend reversed and in 2013, for the first time in the last two and a half decades, the agrifood trade balance turned positive. The present paper is analyzing the evolution of the trade evolution and its structure, separating the agrifood products in three categories: agricultural commodities, primarily processed products and secondary processed products. A higher ratio of processed products in exports is indicating an increased competitiveness, resulting from higher unit values incorporating more added value, and showing, at the same time, a higher development degree of the country's food industry. The results for total trade show that the processed products represented at most 46% of the Romanian exports, and at least 63% of imports, indicating a low-competitive structure of the agrifood trade. The analysis is detailed for intra and extra-EU trade and by main partners and groups of products.
Keywords: 330; agrifood trade; competitiveness; processed products